Different marks in the pitch constraint youth players’ performances during football small-sided games - Coutinho, Diogo (2019)
Purpose: This study aimed to compare players' performances when manipulating the external markings of the pitch during football small-sided games. Methods: Ten under-15 players performed a 5-a-side (plus goalkeepers) under three conditions: (i) Lines, the game was played in a pitch in which the external boundaries were painted with full lines; (ii) Dashed, the game was played in a pitch in which the external boundaries were painted with dashed lines; (iii) Corners, the game was played in a pitch were the external boundaries were delimited by one marker at each pitch corner. Players' positional data was used to compute tactical and time-motion variables. Also, technical analysis was comprised using video footage. Results: Results showed similar tactical, physical and technical performances between the Lines and Dashed conditions. In contrast, the Lines condition showed small higher effects than Corners scenario in the time spent synchronized in longitudinal and lateral displacements, game pace, total distance covered, distance covered while jogging, number successful dribbles and shots on target. The Lines scenario has also revealed a lower effective playing space, distance covered at walking and running and a lower number of passes (small effects) compared to Corners. Conclusions: These results highlight that these changes in informational perception constraints modify players movement behavior. Accordingly, pitches with more visible boundaries were likely to decrease team dispersion, which may optimize team synchrony and technical performances, while decreasing the distance covered at higher speeds. Coaches may use this information to modify the types of pitch external boundaries markings, exposing the players to different environmental information.